Potential health effects of pesticide use on farmworkers in Lesotho - Mokhele, Tholang (South African Journal of Science, 2011)
This study examined the experiences of farmworkers during crop spraying in Lesotho. The main goal of this study was to determine the perceptions and awareness of farmworkers regarding the use of pesticides and the potential effects on their health. The data were obtained from farmworkers using a combination of an open-ended and a close-ended structured questionnaire in July 2006. Of the nine farms serviced by the Ministry of Agriculture and Food Security of Lesotho, Agricultural Research Division, six farms were randomly chosen and 27 farmworkers from these farms were interviewed. The data were analysed using descriptive statistics such as frequency tables. The results showed that farmworkers are relatively poorly educated and that a greater health risk is present when a lack of training and education on the use of pesticides also exists. That is, the majority (85%) of farmworkers did not have secondary education and most (93%) had no training on the use of pesticides, which poses a great health threat to the farmworkers. A lack of education makes it difficult for farmworkers to read and understand the information labels on pesticides and hence it is difficult for them to understand the health hazards of pesticides and the need for personal safety measures. When using and handling pesticides, 52% of farmworkers did not use rubber gloves and 93% did not use goggles or other forms of face cover. This lack of protection puts them at serious risk of skin exposure to pesticides. The farmworkers were quite aware of the harmful effects of pesticides, but were sometimes unable to translate this awareness into their own safety practices because of a lack of knowledge about the adverse effects. Therefore, training, extension services and various awareness programmes should be promoted in Lesotho in order to increase farmworkers' knowledge and awareness of the adverse effects of pesticides on human health and the environment.